Treating acute myeloid leukemia among children with down syndrome - Kapoor, Rajan; Mohan, Karthik Ram; Roy, Shuvendu; Pramanik, Suman Kumar; Khera, Sanjeev; Simalti, A K (Indian Journal of Medical and Paediatric Oncology, 2020)
Background: Down Syndrome (DS) children with acute myeloid leukemia (AML) have unique differences in clinical features, epidemiologic nature, and biologic patterns of disease compared with AML in children without DS. Aims and Objective: AML in DS children should be considered distinct disorder from AML in Non DS population and treatment needs to be customized for this population. In this retrospective study spanning from 2014 to 2019 we present our experience of managing leukemia in children with DS. Materials and Methods: From 2014 and 2019, 72 children aged below 18 years were managed at our institute with acute myeloid leukemia (AML). Out of these 72 children with AML, 7 children were with DS which was confirmed by karyotyping. Majority of these children had M7 while M2 and M4 subtypes were seen in one child each. On conventional karyotyping in addition to trisomy 21 additional cytogenetic abnormalities were seen in 4 patients. Two children had trisomy 8. One child had deletion of 11 chromosomes and one had translocation between 8 and 21 chromosomes. Results: All 7 children were administered intensive chemotherapy with curative intent after informed parental consent. All 7 children achieved complete remission. Four out of 7 children had complications related to severe neutropenia. Conclusion: All patients of DS with AML should be offered chemotherapy with curative intent. Endeavour should be to give less aggressive chemotherapy protocol to bring down treatment related mortality.
Keywords: Acute myeloid leukemia; curative intent; Down syndrome